A Rare Case of Successfully Treated Total Anomalous Systemic Venous Connection With Interruption of IVC in an Adolescent. Issue 3 (September 2022) - Mahadevappa, Manjappa; Reddy, Chinnaswamy; Kulkarni, Prashanth
Total anomalous systemic venous connection (TASVC) with interruption of inferior vena cava in the absence of heterotaxy is an extremely rare anomaly. TASVC is diagnosed when both the caval veins and coronary sinus drain into the left atrium. The diagnosis of TASVC is possible only when all the systemic veins (both superior and inferior caval veins) and coronary sinus drain into the left atrium in the setting of normal or mirror-imaged atrial arrangement. The presence of cyanosis despite left-to-right shunt across an atrial septal defect with hypoplastic or small right heart chambers should arouse the suspicion of TASVC. The severity of symptoms and the age of presentation depend highly on mixing at the atrial level across the atrial septal defect. The amount of mixing also decides the growth of the right atrium, right ventricle, main and branch pulmonary arteries. Adequately sized right heart chambers and tricuspid annulus with good mixing at the atrial level facilitate complete correction and event-free survival. Prompt diagnosis is possible with contrast echocardiography performed both from upper and lower limb veins, cath study, and cardiac computed tomography or magnetic resonance imaging. However, it is not uncommon to note that even in the era of advancement in echocardiography, the complete miss diagnosis of this entity as single ventricle physiology and denial to the patient of possible complete surgical correction. We are reporting here a case of successfully treated TASVC with interrupted inferior vena cava in an adolescent.